Cultivating women's empowerment through agritourism: Evidence from Andean communities - Gil Arroyo, Claudia (2019)
Tourism has the potential to empower women, particularly in rural areas. However, little is known about whether it can have the same effect in Andean communities, mainly because the traditional social and cultural structures of those communities have limited women's ability to empower themselves through traditional economic activities. Through interviews with residents participating in agritourism development in seven communities across the Cusco and Puno regions (Peru, South America), this study examined the role of agritourism development in the empowerment of women in those communities as well as the ways in which it has changed traditional gender roles. Study findings revealed that agritourism contributes to four areas of empowerment for women: psychological, social, political, and economic. However, the culture of the Andean communities still has considerable influence on gender dynamics and may prevent women from garnering all the benefits of tourism development. Agritourism development in those communities should incorporate gender-related cultural considerations to navigate and overcome barriers, thereby allowing the maximization of empowerment benefits for women.